Epidemiological characterization of imported recurrent Plasmodium vivax and Plasmodium ovale in China, 2013-2020 - Yanwen Cui; Li Zhang; Zhigui Xia; Hejun Zhou; Fang Huang (BMC, 2021)
Abstract Background China has reached important milestones in the elimination of malaria. However, the numbers of imported recurrent cases of Plasmodium vivax and P. ovale are gradually increasing, which increases the risk of malaria re-establishment in locations where Anopheles mosquitoes exist. The aim of this study is to characterize the epidemiological profiles of imported recurrent P. vivax and P. ovale cases, quantifying the recurrence burden and guiding the development of appropriate public health intervention strategies. Methods Individual-level data of imported recurrent P. vivax and P. ovale cases were collected from 2013 to 2020 in China via the Parasitic Diseases Information Reporting Management System. Demographic characteristics, temporal and spatial distributions, and the interval from previous infection to recurrence were analyzed by SAS, ArcGIS and GraphPad Prism software, respectively, to explore the epidemiological profiles of imported recurrent cases. Results A total of 307 imported recurrent cases, including 179 P. vivax and 128 P. ovale cases, were recorded. The majority of cases occurred in males (P. vivax 91.1%, P. ovale 93.8%) and migrant workers (P. vivax 43.2%, P. ovale 44.7%). Individuals aged 30-39 years had the highest P. vivax and P. ovale recurrent infection rates, respectively. The number of imported recurrent cases of infection by these two malaria species increased from 2013 to 2018, and P. vivax infection showed well-defined seasonality, with two peaks in February and June, respectively. More than 90% of patients with recurrent cases did not receive radical treatment for previous infection. Most imported recurrent P. vivax cases were reported in Yunnan Province and were imported from Myanmar, Ethiopia, and Pakistan, while most recurrent P. ovale cases were reported in southern China and primarily imported from Cameroon, Ghana, and Nigeria. The intervals from previous malaria infection to recurrence among different continents were significantly different (P = 0.0016) for P. vivax malaria but not for P. ovale malaria (P = 0.2373). Conclusions The large number of imported recurrent cases has been a major challenge in the prevention of malaria re-establishment in China. This study provides evidence to guide the development of appropriate public health intervention strategies for imported recurrent P. vivax and P. ovale cases. Graphic abstract